IMPLEMENTASI METODE GOAL PROGRAMMING UNTUK OPTIMASI PRODUKSI KOPI PADA UMKM KOPI NAKA - Nurul Hidayat; Rizha Nurul Hidayah; Alya Ramadani; Nailla Mariana; Nabila Nabila; Usman Ali; Edowardus Edowardus (CV. Denasya Smart Publisher, 2026)
Kopi Naka is a micro, small, and medium enterprise (MSME) operating in the coffee beverage sector, located in Tarakan, North Kalimantan. Kopi Naka produces several signature iced coffee variants, namely Naka (Milk Coffee), Naren (Palm Sugar), Namel (Caramel), Nalla (Vanilla), Nacho (Chocolate), and Nalo (Milo). In its daily operations, production quantities are still determined based on estimated demand, which often leads to suboptimal results. This study aims to optimize the production of Kopi Naka's signature menu using the goal programming method with the assistance of the POM-QM version 5.2 software. The objectives to be achieved include fulfilling the targeted production quantity, minimizing production costs, and maximizing profits. The optimization results indicate that all priority goals can be optimally achieved. The production capacity target of 1,400 cups per month can be met through a recommended production combination of 1,355 cups for the Naka variant and 45 cups for the Nacho variant. Through this production combination, Kopi Naka MSME can achieve an optimal profit target of IDR 3,245,000 per month, with an efficient production cost utilization of IDR 11,200,000 per month (achieving a savings of IDR 40,000 from the total estimated cost constraint of IDR 11,240,000).